Christmas jars : the miracle of one jar - Jang, Krista; Lea, Ron; Leverman, Zerha; Murray, Doug; Ross, Jeni; Tarasiuk, Markian; Yelland, Tara; Boucher, Shane; Stevens, Andrea; Wright, Jonathan, 1970-; Wright, Jason F.; BYU Television (Provo, Utah); et al. (Provo, Utah BYU TV, 2019)
Hope is an aspiring reporter who was abandoned by her mother at birth. She's grieving the recent death of her adopted mother when her apartment is burglarized of all her possessions. While reporting the burglary to the police, Hope discovers a jar full of money, labeled "Christmas Jar." Shocked and grateful for this act of kindness, Hope discovers that people all over her hometown of Columbus, Ohio, have been receiving Christmas jars for years during times of need. In this Christmas classic, Hope goes undercover to discover the secret behind the Christmas jars, putting into motion a series of events that will change her life, and her community, forever.
Based on the novel by Jason F. Wright.
Special features: cast interviews, author interview.
Title from container.
Widescreen.
Baseed on the novel by Jason F. Wright.
Jeni Ross, Markian Tarasiuk, Tara Yelland, Doug Murray, Krista Jang, Ron Lea, Zerha Leverman.
Keywords: Abandoned children -- Drama; Adoption -- Drama; Adoptive parents -- Drama; Burglary -- Drama; Generosity -- Drama; Kindness -- Drama; Secrecy -- Drama; Women journalists -- Ohio -- Columbus -- Drama; Columbus (Ohio) -- Drama; Ohio -- Columbus; DVD-Video discs; Video recordings for the hearing impaired; Film adaptations; Christmas films; Drama; Feature films; Fiction films